2021
DOI: 10.1002/oby.23182
|View full text |Cite|
|
Sign up to set email alerts
|

Protecting individuals living with overweight and obesity: Attitudes and concerns toward COVID‐19 vaccination in Canada

Abstract: Objective The aim of this study was to assess attitudes toward coronavirus disease 2019 (COVID‐19) vaccination and the degree of fear of COVID‐19 among those living with obesity. Methods Two samples were recruited for an online survey: one sample was a representative sample of Canadians living with overweight and obesity (n = 1,089), and the second was a convenience sample of individuals recruited from obesity clinical services or patient organizations (n = 980). Respondents completed ratings of their comfort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
(23 reference statements)
2
18
0
Order By: Relevance
“…People who were obese were less likely to accept the COVID-19 vaccination. Our findings are in accordance with a study from Canada showing that obese people were more ambivalent about COVID-19 vaccination but contrast with a study from Kuwait that found overweight and obese people were more likely to get the vaccine [60,65]. Such variations could be explained by differences in public perceptions and health beliefs about vaccination between countries.…”
Section: Discussionsupporting
confidence: 88%
“…People who were obese were less likely to accept the COVID-19 vaccination. Our findings are in accordance with a study from Canada showing that obese people were more ambivalent about COVID-19 vaccination but contrast with a study from Kuwait that found overweight and obese people were more likely to get the vaccine [60,65]. Such variations could be explained by differences in public perceptions and health beliefs about vaccination between countries.…”
Section: Discussionsupporting
confidence: 88%
“…Widespread vaccine uptake has been essential in reducing COVID-19 related morbidity and mortality, but also in slowing transmission of the virus and the potential emergence of more life-threatening variants. [ 12 ] Yet less is known about vaccine intention in people with obesity, [ 13 , 14 ] and specifically those who have undergone bariatric surgery. Research conducted in the general population, prior to the U.S. vaccine rollout in December 2020, [ 15 ] suggested that demographic differences, such as being female, younger, lower educational attainment, or belonging to certain ethnic minority groups were associated with greater vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 – 20 ] Similar apprehensive attitudes were observed in the only published study to date, on COVID-19 vaccine attitudes among a sample with obesity. [ 14 ] In June to October 2020, researchers surveyed adults with obesity in Canada and found that approximately 40% were vaccine hesitant and many had low confidence in a COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…The paradox, however, lies in that some bariatric surgery candidates might not have received COVID-19 vaccines before their surgery out of choice in some countries, while in others, access to the COVID-19 vaccines is scarce; this situation makes decision-making about elective surgeries even more challenging [ 10 ]. The public trust in COVID-19 vaccines is a little disappointing around the world [ 10 12 ]; however, it is not feasible to force patients to get vaccinated before their surgery either. Although vaccination is preferred from a medical perspective, not all patients can be expected to be fully vaccinated, especially those in countries that are behind on their vaccine schedules or lack sufficient vaccine supplies.…”
mentioning
confidence: 99%
“…All vaccinated persons should know that full vaccination does not guarantee immunity from COVID-19, and as surgeons, we should adhere to the safety protocols just as our patients do. The reason is that if bariatric patients contract COVID-19 during the postoperative convalescent period, the risk of thromboembolic events and hospitalization becomes significant due to their low oral intake and limited physical activity [ 8 , 9 , 12 , 16 ].…”
mentioning
confidence: 99%